READ WRITE EASY Research, practice and innovation in deaf multiliteracies (Volume 2) - Zeshan, Ulrike (Ishara Research Series, 2021)
This book is the second of two volumes on deaf multiliteracies based on research with deaf children and adults in India, Uganda and Ghana. Multiliteracies include not only reading and writing but also skills in sign language, drawing, acting, digitally mediated communication, and other modes. The book covers a variety of themes including learner engagement, classroom practice, capacity building, and education systems. Authors discuss aspects of learning such as the sequencing of different multiliteracies skills in the classroom, a gamified approach to English grammar, a sign-bilingual online environment, and the influence of visual materials on learners' participation. Capacity building with young deaf professionals and a comparative discussion of deaf education systems in three countries also feature in the volume. The book is of interest to both researchers and practitioners. In addition to four research chapters, it features four 'innovation sketches'. These are reports of innovative practices that have arisen in the context of the research, and they are particularly relevant for practitioners with an interest in methodologies.